Growth potential of three strains of Listeria monocytogenes and Salmonella enterica in Frescal and semi-hard artisanal Minas microcheeses: Impact of the addition of lactic acid bacteria with antimicrobial activity. (15th March 2022) - Campagnollo, Fernanda B.; Pedrosa, Geany T.S.; Kamimura, Bruna A.; Furtado, Marianna M.; Baptista, Rafaela C.; Nascimento, Henry M.; Alvarenga, Verônica O.; Magnani, Marciane; Sant'Ana, Anderson S.
Abstract: This study aimed to determine the growth potential (δ) of L. monocytogenes (CLIST 3974, CLIST 3969, and CLIST 4162) and S. enterica [ S. Typhimurium (ATCC SM 14028), S. Enteritidis (SM 64), and S. Montevideo (SM 129)] in the presence of a pool of lactic acid bacteria (LAB) with antimicrobial activity in Frescal and semi-hard Minas microcheeses. The δ was determined after storing Frescal cheese at 4 and 7 °C for 15 days and the and semi-hard Minas cheese during ripening (22 °C for 22 days). The δ of L. monocytogenes was significantly higher in Frescal Minas cheese with no added LAB (p > 0.05). On the other hand, in semi-hard cheese inoculated with LAB, inactivation of L. monocytogenes was observed. No significant differences were found in the δ of S. enterica in Frescal Minas cheese inoculated with LAB at 4 and 7 °C. S. enterica SM 14028 and SM 129 could grow in semi-hard cheeses non-inoculated with LAB, while when LAB was inoculated, S. enterica was inactivated. The findings of this study indicated that the δ of L. monocytogenes strains was more affected in cheeses inoculated with LAB than the δ of S. enterica . Highlights: Selected lactic acid bacteria (LAB) impact the Listeria growth in Minas Cheese. LAB caused inactivation of L. monocytogenes in semi-hard cheese. Effects of LAB on S. enterica growth varied with cheese type and strain tested. LAB influenced the ending pH for all treatments, regardless the cheese type.